L’incidence de la pol ypose nasosinusienne dans la population de Laghouat - HADJI AMIRA; GASMI MOSTAFA (My University, 2023)
This prospective study aimed to assess the incidence of chronic rhinosinusitis with nasal polyps (CRSwNP) in the general Algerian population. CRSwNP is a chronic inflammatory condition characterized by multifocal and bilateral edematous degeneration of the nasal sinus mucosa, leading to the formation of polyps in the nasal cavities. Although it is common (1 to 4% of the population), the pathophysiology of CRSwNP remains poorly understood. The primary objective of this prospective study was to determine the incidence of CRSwNP, and secondary objectives included evaluating the association between CRSwNP and asthma, as well as the percentage of patients requiring surgical management. Our sample included 716 patients consulting in Otolaryngology, aged over 18 years. Informations were collected through clinical examination and endoscopy. Preliminary results revealed an incidence of 1.67% of CRSwNP in the analyzed sample, with a male predominance. The main symptoms observed were nasal obstruction, olfactory disorders, anterior rhinorrhea, nasal itching, and sneezing. Endoscopic examination showed the presence of bilateral translucent grape-like polyps, predominantly at stage II. Among patients with CRSwNP, 66.7% had isolated CRSwNP, and 33.3% presented with Widal syndrome. No cases of association between CRSwNP and asthma were observed, highlighting the importance of studying the immunological profile of Algerian patients, considering that both asthma and CRSwNP involve Th2 inflammation. The primary treatment approach was medical, based on corticosteroid therapy, and no cases of corticosteroid resistance were observed. No patients underwent surgical intervention during the study period.
86 p.